The tragedy of Molėtai jews and issues of fraudulent records filed at court - Zagreckas, Rimantas (Genocidas ir rezistencija, 2018)
One of the largest sets of documents preserved at Lithuanian archives reflecting the history of our country during the first Soviet occupation (1940–1941) and after World War II is the Fund of Criminal Cases. The Fund was compiled by the Committee for State Security (KGB – Komitet Gosudarstvennoy Bezopasnosti) and at present is stored at Lithuanian Special Archives. In Soviet times, this collection of records was not accessible to both professional historians and the general public. The set contains numerous documents marked Top Secret. It has been always believed that forgery of such type documents is unlikely. Historians investigating the stalinist era of the history of the Soviet Union have no doubts regarding fraudulent lawsuits filed against ideological opponents or any people, by whom the regime was dissatisfied. Falsification used to be a tool to deal with an enemy. At first sight, many would think that such a case in Lithuania must be different, as the fight against Soviet authorities used to be real in our country (in particular, during post-war period); unlike the events that took place in the fourth decade of the 20th century in Russia, for example.This article contains material, proving that KGB was not interested in collecting evidence as accurate as possible. The persons invited by the KGB to present evidence did not provide exact data, while the KGB just wanted to send to prison unwanted persons for a longer time. The author has justified this fact on the basis of interrogation material of a platoon of Lithuanian rebels that was operating in 1941 in Utena county Molėtai town. The rebels contributed markedly to Jews killing by shooting to death. Moreover, the material examined by the author demonstrates systemic unruliness of that time courts, when the accused were not permitted to be provided with services of lawyers, their dissatisfaction with a trial could only be expressed through cassation complaints. All this encumbers the general assessment of such cases as well as recovery of historical facts, among them those related to the Holocaust. When examining the lawsuits filed by the KGB, the application of the comparative method should prevail in terms of number of cases being examined: material of several cases should be collated and only then conclusions drawn.
Keywords: Lithuania; Molėtai; german occupation; jews; Holocaust